2020
DOI: 10.1002/ptr.6877
|View full text |Cite
|
Sign up to set email alerts
|

Insights to potential antihypertensive activity of berry fruits

Abstract: Hypertension is one of the main risk factors for cardiovascular disease and causes widespread morbidity and mortality worldwide. Although several antihypertensive drugs have been proposed for management of high blood pressure, changing lifestyle, including diet, has attracted interest recently. In this sense, consumption of fruits and vegetables, which are rich in vitamins, minerals, and phytochemicals, has been assigned as an efficient therapeutics. Berry fruits contain various bioactive compounds with potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…The absorption band for A. bracteosa appearing in the range of 500–4000 cm –1 is due to the presence of functional groups such as carboxylic acid, phenolics, esters, and saccharides. 39 Polyphenols are known to have beneficial effects on hypertension by acting as antioxidant, anti-inflammatory, and endothelium-modulating agents 40 The HPLC analysis of the A. bracteosa extract identified qurecetin, gallic acid, caffeic acid, vanillic acid, benzoic acid, syringic acid, p -coumaric acid, ferulic acid, and coumarin, which forms the basis for the use of A. bracteosa as an antihypertensive agent. As mentioned, the A. bracteosa extract used in the present study contained flavonoids including quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption band for A. bracteosa appearing in the range of 500–4000 cm –1 is due to the presence of functional groups such as carboxylic acid, phenolics, esters, and saccharides. 39 Polyphenols are known to have beneficial effects on hypertension by acting as antioxidant, anti-inflammatory, and endothelium-modulating agents 40 The HPLC analysis of the A. bracteosa extract identified qurecetin, gallic acid, caffeic acid, vanillic acid, benzoic acid, syringic acid, p -coumaric acid, ferulic acid, and coumarin, which forms the basis for the use of A. bracteosa as an antihypertensive agent. As mentioned, the A. bracteosa extract used in the present study contained flavonoids including quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the effects of the methanol extract of the leaves of C. zeylanicum and its ethyl acetate fraction on arterial hypertension and the renal function were evaluated in L-NAME treated rats. It has been extensively shown that polyphenols, especially flavonoid compounds, possess antihypertensive effects and that this activity is closely related to their antioxidant capacities [ 21 23 ]. Based on this knowledge, we hypothesized that C. zeylanicum extracts may induce their claimed antihypertensive effects thanks to their content in polyphenols and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, phenolic compounds such as flavonoids, and ellagitannins in berries like strawberry (Fragaria × ananassa), blueberry (Vaccinium corymbosum), or raspberry (Rubus idaeus), and seems to have played an important role in the modulation of chronic hypertension (Yousefi et al, 2020).…”
Section: Antihypertensive Activitymentioning
confidence: 99%